Smokers who are also using smokeless tobacco products in the US: A national assessment of characteristics, behaviours and beliefs of 'dual users' - Regan, Annette; Berkowitz, J. (BMJ Publishing Group, 2011)
Background Marketing and advertising of smokeless tobacco products towards cigarette smokers has increased recently. Because the use of multiple tobacco products is a growing public health concern, the present work assesses the use of smokeless tobacco among cigarette smokers, a behaviour termed as 'dual use', as well as attitudes and beliefs on their 'dual use' of tobacco. Methods Data were used from the 2008 ConsumerStyles survey, a nationally representative, mail-in survey of consumers in the USA (n1/410 108). Results 'Dual use' was more common among cigarette smokers who were young, white men living in the Midwest or South. The majority of 'dual users' reported using smokeless tobacco in places where they could not smoke (67.7%) and did not believe smokeless tobacco would help in quitting smoking (75.1%). 'Dual users' reported planning to quit within the next 6 months less often than adults who smoke cigarettes exclusively and close to half (42.3%) never plan to quit smoking. Conclusions Tobacco use is attributed to a number of diseases and deaths worldwide, and cessation of tobacco use can reduce these health risks. The prevalent use of smokeless tobacco in places with smoking restrictions and lack of planning to quit by 'dual users' suggest the need to promote cessation among these users.